Early Assessment of the Risk of Developing Subclinical Hypothyroidism and Cardiovascular Risk in Patients with Nonalcoholic Fatty Liver Disease - Kolesnikova, Olena; Nemtsova, Valeriya; Isayeva, Anna (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Background: It is known that the presence of subclinical hypothyroidism (SH) can worsen the course of non-alcoholic fatty liver disease (NAFLD). NAFLD, in turn, promotes the hypofunction of the thyroid gland. Risk of cardiovascular events is increased in patients with SH, but data on the SH screening recommendations are controversial and limited. Objective: To assess the risk of developing subclinical hypothyroidism (SH) in patients with non-alcoholic fatty liver disease (NAFLD) with a different risk of cardiovascular complications, and to identify the link between high risk of developing SH and major cardiovascular factors (CV). Material and methods: A one-stage clinical trial included 298 people with NAFLD with the presence of one or more CV risk factors (arterial hypertension, smoking, hypercholesterolemia) and various levels of CV risk factors on the SCORE scale. All patients were questioned on a standard questionnaire and HRQ, a thyroid status study was conducted. Result: Patients were divided into three groups according to the level of total CV risk for SCORE: 33.9% had low / moderate CV risk, 41.9% - high and 24.2% - very high CV risk. The majority of the subjects were in the age groups 50-59 and 60-69 years. In the age group 40-49 years, 22.2% of patients had high CV risk, 28% of men aged 50-59 years had moderate CV risk, while 49.7% of older patients showed very high CV risk. According to the results of a survey on the HRQ questionnaire, a low risk of developing hypertension was found in 34.9%, a moderate risk in 48.9%, and a high risk was found in 16.1% of patients. Persons with a very high CV risk on the SCORE scale also have a high risk of developing the SH according to the HRQ questionnaire. Among patients with the presence of one or more of the above CV risk factors, early markers of thyroid status disorders should be identified and the risk of developing hypertension should be assessed. Such a tactic contributes to an adequate assessment of the risk of SH in patients with NAFLD and the development of methods for primary prevention.